Cardiovascular disorders in children with COVID-19 - V.V. Yevtushenko; I.Yu. Seriakova; S.O. Kramarov; N.S. Kyrytsia; V.O. Shadrin; O.O. Voronov (Zaslavsky O.Yu., 2023)
Background. The purpose of the work is to study the prevalence of cardiac disorders in hospitalized children with coronavirus disease (COVID-19). Materials and methods. A retrospective, cohort, monocenter study of the medical records of children who underwent inpatient treatment between September and December 2021 at the Kyiv City Children's Clinical Infectious Disease Hospital was conducted. For our study, we selected the medical records of patients with polymerase chain reaction-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the presence of at least one result of cardiac activity examination by electrocardiography (ECG) and/or echocardiography. The first study of cardiac activity by ECG and/or echocardiography was carried out in the first three days of inpatient treatment. Standard methods of descriptive statistics were used for data processing. Non-parametric statistical methods (Mann-Whitney test, chi-square, Pearson's exact test) were used for mathematical analysis. The research was carried out in accordance with the Declaration of Helsinki principles. The study was approved by the bioethics committee of the hospital. Results. Among 305 children hospitalized with a diagnosis of U07.1 (2019-nCoV acute respiratory disease), there were selected 195 medical histories of patients aged 15 days to 18 years (median of 5.37 years), who were examined for cardiac activity by ECG and/or echocardiography. The most common changes were rhythm disturbances in the form of sinus tachycardia (20.8 %), bradycardia (11.9 %) and sinus arrhythmia (7.9 %), ventricular conduction disorders (25.7 %), deviation of the electrical axis of the heart (10.9 %) and repolarization disorders (31.7 %). During echocardiographic examination, structural abnormalities in the form of myocardial hypertrophy were detected in 3.1 % of patients, dilated heart chambers in 2 %, and pericardial effusion in 9.2 %. Among the functional changes, we observed: a decrease in left ventricular contractility in 4.1 % of cases, in cardiac output in 28.6 %, and an increase in total peripheral resistance in 41.8 %. Heart rhythm disturbances in the form of sinus tachycardia, deviation of the electrical axis of the heart, a decrease in the amplitude of the ECG waves, repolarization disorders, and pericardial effusion were associated with an increased risk of death in children with COVID-19. Clinical cases of cardiovascular complications in the form of jugular vein thrombosis and infectious endocarditis illustrate the role of the cardiovascular system in the pathogenesis of coronavirus disease. Conclusions. SARS-CoV-2 infection is often associated with damage to the cardiovascular system. In most pediatric patients, this occurs in the form of subclinical changes registered during laboratory or instrumental studies, but the development of manifest forms such as myocarditis, endocarditis, pericarditis, heart attack, coronary disease, thrombotic complications, and heart failure is possible. Using simple non-invasive methods (ECG and echocardiography) during screening, it is possible to diagnose damage to the cardiovascular system, as well as to detect changes in the cardiovascular system, which are subclinical, but can have an important prognostic value regarding the adverse course of the disease in children, which are hospitalized with SARS-CoV-2 infection.